Potential influence of herd and animal factors on the yield of cheese and recovery of components from Sarda sheep milk, as determined by a laboratory bench-top model cheese-making. (December 2016) - Cipolat-Gotet, Claudio; Cecchinato, Alessio; Pazzola, Michele; Dettori, Maria Luisa; Bittante, Giovanni; Vacca, Giuseppe Massimo
Abstract: Individual milk samples from 169 Sarda sheep were collected to characterise the cheese-making potential through the use of a laboratory bench-top model cheese-manufacturing procedure. As the milk samples were not standardised before processing, the data collected at laboratory level fully reflected the great variability of milk from individual animals. The average cheese yield traits of fresh cheese, cheese dry matter and water retained in cheese (as percentages of the milk processed) were 20.6%, 10.1% and 10.6%. The average milk fat and protein recoveries in the curd were 94.0% and 76.7%, respectively. The values for daily production of curd and curd dry matter per sheep were 0.41 kg d −1 and 0.20 kg d −1, respectively. The cheese yield and cheese-related traits were mainly affected by the nutrient content of the milk and the individual effects of the stage of lactation and daily milk yield, respectively, but also by a large individual variation.